A Note on the Petroleum Industry's Participation in Conservation Agreements for the Lesser Prairie Chicken. (16th October 2018) - Melstrom, Richard T.
Abstract : This paper examines the petroleum industry's willingness to participate in conservation agreements for the lesser prairie chicken, a candidate for listing under the Endangered Species Act (ESA). Voluntary conservation agreements with assurances (VCAAs) can incentivize habitat conservation and sustain economic development. Using data on oil and natural gas wells in Kansas and Oklahoma, I develop a discrete choice model to examine company preferences for locating wells and participating in VCAAs for the lesser prairie chicken. Participation in VCAAs is low, but I find participating wells are concentrated in areas with the most crucial habitat.